Seroprevalence and postmortem lesions of contagious bovine pleuropneumonia in selected abattoirs and dairy farms in South Wollo Zone, Northeast, Ethiopia - Bekele, Juhar Tesfaye; Gizaw, Tarekegn Tintagu; Worku, Yalelet; Ulo, Yasin Beriso; Bekele, Tilahun; Alemu, Bethelehem; Alemayehu, Alula (Archives of Veterinary Science, 2024)
Contagious bovine pleuropneumonia is a highly contagious respiratory disease of cattle. A cross-sectional study was conducted from December 2019 to August 2020 to determine the seroprevalence, suggestive lesions prevalence, and factors associated with contagious bovine pleuropneumonia in selected abattoirs and dairy farms of the south Wollo zone, Ethiopia. A total of 384 (local and cross-breed) animals, 192 from dairy farms and 192 from abattoirs were selected using simple random and systematic random sampling techniques respectively. For serological investigation, blood samples were collected from each animal, and sera were harvested and subjected to competitive- enzyme-linked immunosorbent assay (c-ELISA at the National Veterinary Institute of Ethiopia. Of the 384 sera, thirteen (13/384) were found to be positive with an overall prevalence of 3.4%. Seroprevalence of contagious bovine pleuropneumonia (CBPP) was statistically significantly associated with body condition (P-value =0.001, OR=9.7) and age (P-value= 0.037, OR= 3.28). However, the sex, breed, and origin of the animals were not statistically significantly associated with the occurrence of CBPP. Regarding the abattoir survey, all 192 blood-sampled animals were subjected to postmortem examination, and contagious bovine pleuropneumonia suggestive lesions were identified in the lungs of 10 animals and the abattoir survey prevalence was calculated as 5.2%. In the present study, contagious bovine pleuropneumonia suggestive lesions were observed in all seropositive animals and three seronegative animals. This indicated that there was strong test agreement between c-ELISA and postmortem examination (Kappa = 0.816) in the diagnosis of the disease. In postmortem examination of the lungs, suggestive lesions including marbling, hepatization, pleural adhesion, and yellowish fluid in the thoracic cavity were the main gross pathologies. The present findings seem lower but the contagious nature of the disease and its economic significance make it worse so appropriate prevention measures such as annual immunization, movement restriction, and proper management practices should be implemented and continued surveillance at the abattoirs and subsequent epidemiological investigation of suspected cases should be done.